PENGEMBANGAN DESA WISATA STUDI KASUS DI DESA DASUN, KECAMATAN LASEM, KABUPATEN REMBANG - Ulil Albab Alvarelly; Ari Subowo; Augustin Rina Herawati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Tourism villages are one of the policies issued by the Government with the aim of improving the welfare and economy of rural communities. The implementation of the development and development of a tourist village has an important role for stakeholders along with the factors that influence it. This study aims to identify and analyze the role of the stakeholders involved and determine the factors that influence the development of the Dasun Tourism Village. This study used a qualitative descriptive method with data collection techniques through interviews, documentation and observation. The results of the study show that there are stakeholders involved in the development of the Dasun Tourism Village who act as policy makers, coordinators, facilitators, implementers and accelerators. Factors influencing the development of the Dasun Tourism Village were analyzed from the uniqueness of the location, the involvement of the local community, the financing of tourism activities, the role of the driving force and liaison between institutions. So far the development of the Dasun Tourism Village has minimal involvement of stakeholders from outside the scope of government so that the development process still depends on government intervention and there is an inhibiting factor, namely the financing of tourism activities. Suggestions that can be given are tourism actors collaborating with parties outside the government, so that their roles as facilitators and accelerators can run more optimally according to what has been planned.